ESTROPHANE SOME MORPHOGENESIS OF COW BLOOD - Yakubov Muzaffar Alimjonovich; Mukhtarov Elmurad Abdiglomovich (American Journals Publishing, 2022)
The article describes the dynamics of changes in the shape elements of the composition of the blood of cows as a result of the pharmacokinetic and pharmacodynamic effects of the hormonal drug estrophan based on the analysis of the literature.
Keywords: Estrofan, hemoglobin, erythrocyte, cyanide method, lekotsid.